STRATEGI DALAM MERENCANAKAN KAMPANYE DAN POLITIK KOMUNIKASI PEMBANGUNAN - Kustiawan, Winda; Muridayani, Muridayani; Al Ghazali, Rayan; Fahmi, M.Amirul; Ar Rasyid, M. Ridho; Pdg, Arkanuddin (Journal Analytica Islamica, 2023)
One of the most important aspects of a political communication strategy is winning votes. The purpose of this study is to find out the political communication strategies used by candidates to win votes. Political leadership that considers the welfare of all residents of a region is very important for regional leaders. It takes time and process to become a good leader. Leadership is the ability to persuade others to do something the leader voluntarily wants. Regional heads can function as political officials and lead government in their regions, leaders must have an understanding of organization and society. The steps that will be designed by the government and implemented by the regions will make a tremendous difference to the areas to the community-oriented public services that will be offered. Provision of public services for the benefit of its citizens is the responsibility of the government as an institution. In addition, the state is obliged to fulfill the basic needs and rights of every citizen and citizen.